2012
DOI: 10.2343/geochemj.1.0136
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal distribution in recent sediments along the Tiet^|^ecirc; River basin (S^|^atilde;o Pauro, Brazil)

Abstract: Variations in the aquatic environmental conditions can produce a release of heavy metals from the sediment to the water resulting in an increase of their bioavailability and consequent toxicity (Young et al., 1987;Wen and Allen, 1999). This aspect can be further investigated when the samples are analyzed in recent sediments, allowing a detailed study of heavy metals in association with the bioavailable and residual fractions, involving materials of different origins. The distribution and quantification of heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
10
1
1
Order By: Relevance
“…The average concentrations of total heavy metals determined in the Tietê riverbed sediments were much higher than the regional background levels observed by Mortatti et al (2012) at the upper, middle and lower parts of the Tietê River basin. This demonstrates that the Tietê riverbed sediments have been polluted by heavy metals originated by anthropogenic activities along the drainage basin.…”
Section: Concentrations Of Total Heavy Metals On Riverbed Sedimentscontrasting
confidence: 56%
“…The average concentrations of total heavy metals determined in the Tietê riverbed sediments were much higher than the regional background levels observed by Mortatti et al (2012) at the upper, middle and lower parts of the Tietê River basin. This demonstrates that the Tietê riverbed sediments have been polluted by heavy metals originated by anthropogenic activities along the drainage basin.…”
Section: Concentrations Of Total Heavy Metals On Riverbed Sedimentscontrasting
confidence: 56%
“…However, this trend is not proved for all elements, which means that the grain size is not the only factor affecting the metal concentrations. Drains effluents, Organic matter content, lithogenic sources and mineralogical composition of sediments as well as the physical, chemical and biological processes are others factors share in controlling the sediment-heavy metal content (Hang et al, 2009;Mortatti, Meneghelg, & Probst, 2011;Presley, Trefry, & Shokes, 1980).…”
Section: 2mentioning
confidence: 99%
“…Since the study of Martin and Meybeck (1979), which showed that the composition of suspended matter transported by the world's largest rivers, there has been a growing interest to estimate suspended sediment transport in rivers and the elements/chemical compounds associated with them (Horowitz, 2008;Walling, 2013). Some studies stand out for using the comparison of a reference geochemical background, through the calculation of enrichment factors (EF) in bottom sediments (Alves et al, 2010;Amorim et al, 2009;Cotta et al, 2006;Gaillardet et al, 2003;Harikumar and Jisha, 2010;Probst, 2006a, 2006b;Kendall and Doctor, 2003;Kersten and Forstner, 1995;Meybeck et al, 2007;Miller et al, 2007;Mortatti et al, 2012;Mozeto et al, 2003;Nasrabadi et al, 2010;Salomons and Forstner, 1984;Shotyk et al, 2000) as well as in suspended sediments Probst, 2006a, 2006b;Kucuksezgin et al, 2008;Mortatti and Probst, 2010;Ollivier et al, 2011;Radakovich et al, 2008;Viers et al, 2009;Woitke et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For the anthropogenic contribution related to domestic sewage the d 13 C, d 15 N and C:N ratios range from À26 to À22 / oo , from þ7 to þ22 / oo and from 7 to 11, respectively (Barros et al, 2010;Gao et al, 2012;Mayer et al, 2002). In Brazil, the few studies that have evaluated the origin and fluvial fluxes of suspended sediment were conducted in the São Paulo State (Alves et al, 2010;Cotta et al, 2006;Fernandes et al, 2012;Mortatti and Probst, 2010;Mortatti et al, 2012). However, none of these studies have associated suspended sediments to particulate organic matter, with POM was only studied in the Piracicaba River basin, also located in the São Paulo State (Krusche et al, 2002), and in the Guanabara Bay, in Rio de Janeiro State (Carreira et al, 2002) and Babitonga Bay, in Santa Catarina State (Barros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%